2016
DOI: 10.3892/ol.2016.4164
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PREX2 promotes the proliferation and migration of hepatocellular carcinoma cells via PTEN-AKT signaling

Abstract: Abstract. Phosphatidylinositol-3,4,5-trisphosphate Rac exchanger 2 (PREX2), a regulator of the small guanosine triphosphatase Rac, demonstrates an inhibitory effect on the activity of phosphatase and tensin homolog (PTEN). Previously, PREX2 was implicated in the regulation of cell invasion in hepatocellular carcinoma (HCC). However, the exact role of PREX2 in the regulation of HCC cell proliferation and migration, as well as the underlying mechanisms, remains unclear. In the present study, reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…PREX2 has been reported to be upregulated in HCC and to play roles in the regulation of HCC cell proliferation and in CXCL9‐induced HCC migration and invasion . In agreement with these reports, we demonstrated that PREX2 accumulation resulting from either GNMT or HectH9 depletion led to AKT activation and enhanced proliferation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PREX2 has been reported to be upregulated in HCC and to play roles in the regulation of HCC cell proliferation and in CXCL9‐induced HCC migration and invasion . In agreement with these reports, we demonstrated that PREX2 accumulation resulting from either GNMT or HectH9 depletion led to AKT activation and enhanced proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…The dissimilarity between the finding in our study and previous reports could be attributed to the sample size used in different studies (139 pairs in our study vs . 45 pairs in Lan's report and 15 pairs in He's report) . In addition, viral infection could also contribute to these discrepancies.…”
Section: Discussionmentioning
confidence: 87%
“…The sequences of P-Rex2a and P-Rex2b are homologous with those of P-Rex1. 31 , 32 Despite various studies pointing out the oncogenicity of guanine nucleotide exchange factors (GEFs) in multiple cancer types, especially melanoma, breast cancer, glioblastoma, and prostate cancer, the present work unveiled a specific new function of P-Rex1 in the pathogenesis of liver cancer. P-Rex1 knockdown attenuated liver cancer cell proliferation, migration, and xenograft tumor growth by mediating the activation of the HGF signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…These results implied that increased expression of these mutated genes might cause the loss of function on tumor suppression, and contribute to the development of HCC. Other identified genes, including CTNNB1, PREX2, and TERT, facilitate the survival or invasion of HCC cells. In the study, we found that these three genes were upregulated in HCC.…”
Section: Discussionmentioning
confidence: 99%